2019
DOI: 10.1089/vbz.2018.2299
|View full text |Cite
|
Sign up to set email alerts
|

Did the Highly Pathogenic Avian Influenza A(H7N9) Viruses Emerged in China Raise Increased Threat to Public Health?

Abstract: The low pathogenic avian influenza A(H7N9) viruses (LPAI) were first identified in 2013 and have continued to infect humans since then. It was reported in February 2017 that the LPAI H7N9 virus has evolved into highly pathogenic avian influenza (HPAI) viruses, potentially increasing the risk for human and poultry. We in this study overviewed the emergence, epidemiology, and biological characterizations of the HPAI H7N9 viruses for the risk assessment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 33 publications
0
3
0
Order By: Relevance
“…Among them, 125 evolved in a convergent (V/T125A) and divergent (V125A/T) manner. Regarding receptor specificity, the HP H7N9 viruses mostly retained dual receptor binding [52,53] features despite the Q217L mutation [3,9,54], which is capable of switching the specificity to the human-type receptor in H2 [55], H3 [56], H4 [57], and H5 influenza virus. It was previously shown that mutations V125T, S134P, A151T, and L217Q in H7N9 occurred around the HA receptor pocket since 2019 increasing the affinity for avian-type sialic acids while decreasing the affinity for human-type sialic acids [18].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Among them, 125 evolved in a convergent (V/T125A) and divergent (V125A/T) manner. Regarding receptor specificity, the HP H7N9 viruses mostly retained dual receptor binding [52,53] features despite the Q217L mutation [3,9,54], which is capable of switching the specificity to the human-type receptor in H2 [55], H3 [56], H4 [57], and H5 influenza virus. It was previously shown that mutations V125T, S134P, A151T, and L217Q in H7N9 occurred around the HA receptor pocket since 2019 increasing the affinity for avian-type sialic acids while decreasing the affinity for human-type sialic acids [18].…”
Section: Discussionmentioning
confidence: 99%
“…HP H7N9 spread rapidly from the south to the north in chicken flocks, and also possibly by live poultry trade transmission during wave 5 [6][7][8]. To mitigate the impact of HP H7N9 to the poultry industry, a nationwide vaccination campaign with H5/H7(Re-1) bivalent inactivated vaccine was launched in September 2017 [9][10][11]. To address antigenic drift and better match the antigenicity of the prevalent strain, the H7N9 Re-2 vaccine replaced the Re-1 vaccine in December 2018 [10].…”
Section: Introductionmentioning
confidence: 99%
“…During the fifth wave in 2016/17, the emergence of highly pathogenic avian influenza (HPAI) H7N9 viruses raised wide global concern [1]. Compared to low pathogenic avian influenza (LPAI) A(H7N9) viruses, HPAI H7N9 viruses maintained the capacity to bind both human and avian receptors [2] and unreduced transmissibility in mammalian animal models, but exhibited higher virulence and broader tissue tropism [3-5]. Subsequent to 31 human HPAI H7N9 cases being reported in China in the fifth wave, their numbers decreased dramatically from October 2017, with only one additional HPAI H7N9 human case up to February 2018.…”
mentioning
confidence: 99%